(untitled) (The Journal of Psychology and Sociology, 2014)
Quest for growth, to self-actualization is the most important quality a person. Urgent need for self- development, self-improvement is an indicator of personal maturity and at the same time to achieve it. He lives a truly authentic life if realizes the potential of its capabilities. Values are a benchmark in human life, act as a mechanism of social control and are embodied in the behavior. The values for different age stages allows you to enjoy the sensation of pleasure and happiness.The problem of value orientations in adulthood is most relevant as it is connected not only with the personal development of adults, but also to overcome periods of crisis. During this period, the most impor- tant is awareness and rethinking of personal values.The current situation in the country requires a reappraisal of values, since in most cases there has been a change in the traditional values. This situation made the weak natural transmission of cultural and historical experience of the older generation to the younger.The system not the individual alignments remains constant over the life cycle, including mature age. With regard to the dynamics of a system of values in adulthood is a more appropriate term «development», as having a greater value. In relation to an adult, the system of values which is already largely in place, you should not speak of well-defined stages of formation, and on the individual level of development.Modern psychology focuses on the physiological maturation and development of psychological func- tions, personality, learning the individual experiences that define the mental development of the person. From this position, maturity is seen as a result of the processes of development in childhood and adoles- cence. Maturity is seen as a condition of stabilization of personality traits, value orientations determined.Due to the accumulation of knowledge about the different stages of human development, found a significant ontogenetic fact associated with the acceleration of the process of maturation and slowing the aging process, in the field of personality of modern man.The main consequence of these changes, ontogenetic is the extension of the maturity age range, the capacity of the health and personal development.Thus, the maturity of how psychological category takes into account the relationship of man to his own age. Experience a relationship to a particular age group, manifested through the presence of family and experience parenthood. The notion of a mature personality a relatively new acquisition of developmental psychology. The psychological definition of maturity is seen as an active mastery of their environment, sustainable unity of personality traits and value orientations.The results reveal broad prospects for studies of value orientations in adulthood in Kazakhstan, as a start for future human development.